Pemurnian dan Deteksi Serologi Patchouli Mottle Virus pada Tanaman Nilam - Sedyo Hartono; Siti Subandiyah; Aminatun Munawarti; Retno Mastuti; Serafinah Indriani (Jurnal Perlindungan Tanaman Indonesia, 2006)
Patchouli mottle virus (PatMoV) is the most severe disease pathogen and causes substantial losses in many patchouli-producing regions in Indonesia. Serological detection tool  for the disease was developed in this  research. Virus isolation was conducted on Chenopodium amaraticolor resulted on  the homogenous local lesions 6 days after  inoculation. Virus  purification was obtained from 200g inoculated leaves resulted on 2 ml virus solution with the concentration of 1 mg/ml. Polyclonal antibodies were produced on rabbits. Harvested antiserum was used for further virus detection by Indirect-Enzyme linked Immunosorbent assay (I-ELISA) and dot-immunobanding assay (DIBA) techniques. The antibodies were  positively  reacted with purified  viruses, infected field collection of patchouli, and  inoculated C. amaranticolor. On the other hand un-inoculated C. amaranticolor samples and healthy patchouli generated from tissue cultures gave negative reaction with the antibodies. This is the first report of cheap practical antibody production for PatMoV detection in Indonesia.